2017
DOI: 10.1017/s0950268817000486
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of risk prediction scores for surgical site infection or periprosthetic joint infection following joint arthroplasty

Abstract: Accurate identification of individuals at high risk of surgical site infections (SSIs) or periprosthetic joint infections (PJIs) influences clinical decisions and development of preventive strategies. We aimed to determine progress in the development and validation of risk prediction models for SSI or PJI using a systematic review. We searched for studies that have developed or validated a risk prediction tool for SSI or PJI following joint replacement in MEDLINE, EMBASE, Web of Science and Cochrane databases;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
(76 reference statements)
0
32
0
Order By: Relevance
“…We identified 24 research papers, published from 2008 until 2019, which contained statistically significant results from a multivariate analysis. A total of 79 risk factors were identified for the three groups of surgical procedures [ 11 – 13 , 16 , 23 , 36 54 ] ( S1 Table ). Age, ASA class, body mass index (BMI), preoperative length of stay and diabetes were identified as general risk factors from the literature search.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 24 research papers, published from 2008 until 2019, which contained statistically significant results from a multivariate analysis. A total of 79 risk factors were identified for the three groups of surgical procedures [ 11 – 13 , 16 , 23 , 36 54 ] ( S1 Table ). Age, ASA class, body mass index (BMI), preoperative length of stay and diabetes were identified as general risk factors from the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate logistic regression is the most common statistical model used to identify risk factors in longitudinal study design data [ 16 ]. Not all studies report the discriminatory power of the multivariate logistic regression model fitted.…”
Section: Introductionmentioning
confidence: 99%
“…These scores apply to elective total knee arthroplasty (TKA), THA, hip hemiarthroplasty and unicompartmental knee prosthesis. Previous studies focused only on THA, TKA, or both [5,10]. Hemiarthroplasty was included here because although the reason for implantation is a fracture, it is also a clean surgery with similar management to other arthroplasties.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic joint infections (PJI) are associated with important morbidity and increased costs [1]. Previous studies have identified many risk factors for PJI [2e4], and although several risk scores have been developed, their applicability and utility are limited [5]. A recent systematic review concluded that none of the identified risk scores so far could be considered ready for use except one for total hip arthroplasty (THA) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Given the severity of PJI, previous studies have identi ed a tremendous number of risk factors for PJI [6][7][8][9]; they can be divided into the patient (intrinsic factor) and environment (extrinsic factor) and play a crucial part in pre-, intra-or post-operative period. Many blood biomarkers are routinely assessed before joint arthroplasty, but only few are commonly used to guide surgeons in determining patients most at risk of PJI [10].…”
Section: Introductionmentioning
confidence: 99%